Design and Implementation of a Backend System and DevOps Workflow for Interactive Learning Applications - Daniswara Sirwenda, Alfian Bisma; Wibowo, Sasono; Gamayanto, Indra; Rifki, Slamet Ikhvan Nurhana; Ismanto, Ivan; Kurniawan, Michael Christ (Journal of Applied Informatics and Computing, 2025)
English language learning in Indonesia faces significant challenges, including limited vocabulary retention, poor pronunciation, and passive learning methods. The EngVenture application was developed to address these issues by integrating gamification principles with interactive English learning environments. This study aims to design and implement a backend system and DevOps workflow that ensure optimal performance, security, and stability for gamification-based learning applications. The Rapid Application Development (RAD) method was employed, comprising requirements planning, user design, construction, and cutover phases. System requirements were identified through a validated questionnaire (Cronbach's α = 0.89) distributed to 101 respondents from diverse backgrounds. Results indicated that users prioritized data security (90.1%), system speed (91.1%), and secure authentication (69.3%) as critical factors. Based on these findings, a RESTful API-based backend was designed and integrated with Docker, Jenkins, and Nginx, incorporating security features such as JWT authentication, API key validation, and SSL/TLS encryption. Quantitative evaluation over a 20-day period demonstrated significant improvements: 85% faster deployment time (6.23→1.48 minutes), 43.4% reduction in error rate (211→138 errors), 95.7% build success rate, stable API response time (~160ms) under load testing with 1,000 concurrent requests, and near-zero downtime (<5 minutes). This research demonstrates that the integration of structured backend architecture and automated DevOps practices significantly enhances system reliability, deployment efficiency, and user satisfaction in educational technology applications such as EngVenture.